The Seismogenic Potential of the Southernmost Ryukyu Subduction Zone as Revealed by Historical Earthquakes and Slow Slip events - Chen, Sean Kuanhsiang; Wu, Yih-Min; Chan, Yu-Chang (Frontiers in Earth Science, 2022)
The southernmost Ryukyu subduction zone may have a geodetically inferred Mw 7.5 to 8.7 megathrust earthquake in a shallow locked region, the Ryukyu fault. Paleoseismological evidence of historical earthquakes available from the last 417 years indicates that only a 1920 Mw 7.7 earthquake agrees with the inferred magnitude, which occurred extremely near the downdip end of the Ryukyu fault. As slow slip events downdip the locked seismogenic zone may trigger a large subduction earthquake, we investigate how the first observed slow slip events in 2005, 2009, and 2015 initiated downdip the Ryukyu fault interface affect the occurrence of a megathrust. We established possible megathrust earthquake cycles from Mw 7.5 to 8.7 on the Ryukyu fault using constraints from the magnitude-frequency relation based on local historical earthquakes. It showed the b value of 1.2 in the magnitudes greater than Mw 7.0, which is higher than the empirical 1.0 value. The evidence indicates that the recurrence of an event up to Mw 8.7 is longer than the previous thought if the megathrust events follow the observed magnitude-frequency relation. Then, the influence of slow slip events on the megathrust earthquake cycles was quantified using the static stress increase in the stress evolution of earthquake cycles to access the triggering of a potential megathrust. We found that stress perturbations caused by the three slow slip events are generally consistent with the values that have triggered the large interplate earthquakes in several subduction zones. However, the large earthquake has not yet been triggered on the Ryukyu fault after a sequence of slow slip events. If the 1920 Mw 7.7 earthquake is the last rupture of the Ryukyu fault, the earthquake cycle on the Ryukyu fault is very likely, not much close to the end and still ongoing. However, this is not true if the slow slip events are very close to the end of the earthquake cycle and there has been no megathrust earthquake at the fault interface in the last 417 years, as the 2011 Mw 9.0 Tohoku earthquake. Thus, higher potential of a megathrust earthquake may occur in the southernmost Ryukyu subduction zone.